2019
DOI: 10.3390/agriculture9080177
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in Adopting Drip Irrigation for California Organic Spinach: Preliminary Findings

Abstract: The main objective of this study was to explore the viability of drip irrigation for organic spinach production and the management of spinach downy mildew disease in California. The experiment was conducted over two crop seasons at the University of California Desert Research and Extension Center located in the low desert of California. Various combinations of dripline spacings and installation depths were assessed and compared with sprinkler irrigation as control treatment. Comprehensive data collection was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…The greatest yield is on tomatoes, which increased by 232%, followed by beans (180%), maize (95%) and covo (Brassica oleracea var acephala) (59%). Montazar et al (2020) and Postel et al (2001) confirm the significance of drip irrigation in lowincome communities and contend that it holds the key to alleviating a significant share of rural hunger and poverty.…”
Section: Ability To Meet Household Food Requirementsmentioning
confidence: 79%
See 3 more Smart Citations
“…The greatest yield is on tomatoes, which increased by 232%, followed by beans (180%), maize (95%) and covo (Brassica oleracea var acephala) (59%). Montazar et al (2020) and Postel et al (2001) confirm the significance of drip irrigation in lowincome communities and contend that it holds the key to alleviating a significant share of rural hunger and poverty.…”
Section: Ability To Meet Household Food Requirementsmentioning
confidence: 79%
“…The greatest yield is on tomatoes, which increased by 232%, followed by beans (180%), maize (95%) and covo ( Brassica oleracea var acephala ) (59%). Montazar et al ( 2020 ) and Postel et al ( 2001 ) confirm the significance of drip irrigation in low-income communities and contend that it holds the key to alleviating a significant share of rural hunger and poverty. According to ZimVAC ( 2018 ), an average household size of six needs around 10 kg of cereal per month, translating into an annual cereal requirement of 120 kg per household.…”
Section: Results and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced spinach yield was reported for SDI compared to SprI, but SDI had better downy mildew control in the low desert region of California (Montazar et al, 2019). The researchers concluded that there was a need for further developmental work to optimize spinach production when using SDI.…”
Section: Sdi In Comparison To Alternative Irrigation Systems For Horticultural Cropsmentioning
confidence: 99%